2010
DOI: 10.1103/physrevb.82.144523
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-driven electronic localization and phase separation in superconductingFe1+yTe0.5Se0.5<

Abstract: We have investigated the influence of Fe excess on the electrical transport and magnetism of Fe 1+y Te 0.5 Se 0.5 ͑y = 0.04 and 0.09͒ single crystals. Both compositions exhibit resistively determined superconducting transitions ͑T c ͒ with an onset temperature of about 15 K. From the width of the superconducting transition and the magnitude of the lower critical field H c1 , it is inferred that excess of Fe suppresses superconductivity. The linear and nonlinear responses of the ac susceptibility show that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
5
23
0
Order By: Relevance
“…The low-T upturn of resistivity is usually caused by localization of carriers. For example, similar behavior has been observed in crystals Fe 1+δ Te 1−x Se x with x = 0.4 [10] or x = 0.5 [11], and it has been attributed to disorderdriven localization, presumably caused by the excess of Fe. However, the disorder-driven weak localization is an orbital eect which should be suppressed by the perpendicular magnetic eld, causing very characteristic negative magnetoresistance eect.…”
Section: Methodsmentioning
confidence: 62%
“…The low-T upturn of resistivity is usually caused by localization of carriers. For example, similar behavior has been observed in crystals Fe 1+δ Te 1−x Se x with x = 0.4 [10] or x = 0.5 [11], and it has been attributed to disorderdriven localization, presumably caused by the excess of Fe. However, the disorder-driven weak localization is an orbital eect which should be suppressed by the perpendicular magnetic eld, causing very characteristic negative magnetoresistance eect.…”
Section: Methodsmentioning
confidence: 62%
“…It was also shown that incommensurate magnetic order and superconductivity coexist for certain Se concentrations [15,16]. Both, superconducting and magnetic properties are known to critically depend on the iron excess [17,18,19,20,16]. The element Fe occupies two different crystallographic positions: position 2a at (3/4 1/4 0) denoted as a Fe1 position and position 2c at (1/4 1/4 z) with z ≈ 0.70, denoted as Fe2.…”
Section: Introductionmentioning
confidence: 97%
“…Many controversial reports concerning the mutual coexistence/interplay of AFM and SC exist in literature [9] which may be, at least in part, related to different preparation methods. Influence of annealing [23,24,25] and different contents of iron [17,18,19,20,16] have been studied intensively, however, very little attention has been given to the influence of cooling rates [26]. Although the majority of the studies [27,23] report, that the prepared polyor single-crystalline Fe 1+y Te 1−x Se x samples contain, depending on preparation conditions, secondary phases (mostly Fe 7 Se 8 , Fe 3 Se 4 or Fe 3 O 4 ), a study dedicated to clarify whether these phases are just unwanted complication or whether they may play a key role in superconductivity of this system is, so far, missing.…”
Section: Introductionmentioning
confidence: 99%
“…Above x = 0.10, a weak magnetic transition is still present but shifts to lower temperature with increase in Se content and almost vanishes for x = 0.25. At still higher Se compositions, x = 0.4 and 0.5, superconductivity dominates [30]. The onset of superconductivity and the weakening of magnetic transition in compositions from x = 0.15 to 0.50 are illustrated in Figure 2 The dc magnetization of crystals with different composition were studied with magnetic field applied parallel to the crystallographic ab plane, see Figure 3.…”
Section: Crystal Structurementioning
confidence: 99%
“…The effect of substitution on the lattice is studied by XRD. From these data, the lattice parameters are extracted using a Rietveld analysis within the FullProf code and assuming the structure model of an earlier work [30]. Figure 1 (a) illustrates the refined powder XRD pattern for the various compositions.…”
Section: Crystal Structurementioning
confidence: 99%